catena-Poly[[[aquabis(1H-imidazole-κN (3))copper(II)]-μ-naphthalene-1,4-dicarboxylato-κ(2) O (1):O (4)] dihydrate] - Li, Jun-Hua (International Union of Crystallography, 2008)
In the title compound, {[Cu(C(12)H(6)O(4))(C(3)H(4)N(2))(2)(H(2)O)]·2H(2)O}(n), the Cu(II) cation is coordinated by two naphthalene-1,4-dicarboxylate (naph) dianions, two imidazole molecules and one water molecule in a distorted square-pyramidal geometry. The Cu—O bond distance in the apical direction is 0.509 (3) Å longer than the mean Cu—O bond distance in the basal plane. The naph dianion bridges two Cu(II) cations, forming a one-dimensional polymeric chain. The coordinated water molecule is hydrogen-bonded to the carboxylate groups and imidazole ligands of adjacent polymeric chains, forming a three-dimensional supramolecular structure. No π–π stacking is observed in the crystal structure. One solvent water molecule is disordered equally over two positions.